2019
DOI: 10.1158/1541-7786.mcr-18-0359
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Landscape of Ovarian Adult Granulosa Cell Tumors from Whole Exome and Targeted TERT Promoter Sequencing

Abstract: Adult granulosa cell tumor (aGCT), the most common malignant ovarian sex cord-stromal tumor, is characterized by the forkhead transcription factor FOXL2 p.C134W somatic mutation. Late recurrences are relatively common but the molecular mechanisms of relapse or aggressive behavior are not known. The mutational landscape of FOXL2 p.C134W mutation-positive tumors ( = 22) was determined using whole-exome sequencing (WES). An average of 64 coding and essential splice-site variants were identified per tumor. As the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
68
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 33 publications
20
68
1
Order By: Relevance
“…An array CGH analysis of FFPE samples of 40 surgically resected aGCTs confirmed that the most frequent CNV was loss of chromosome 22q; this had occurred in 52% of the primary tumors and 82% of the recurrent tumors. Similar values (ranging from 30 to 53%) have been reported in the literature [10,11,14,15].…”
Section: Chromosome Instability In Recurrent Agctssupporting
confidence: 90%
See 1 more Smart Citation
“…An array CGH analysis of FFPE samples of 40 surgically resected aGCTs confirmed that the most frequent CNV was loss of chromosome 22q; this had occurred in 52% of the primary tumors and 82% of the recurrent tumors. Similar values (ranging from 30 to 53%) have been reported in the literature [10,11,14,15].…”
Section: Chromosome Instability In Recurrent Agctssupporting
confidence: 90%
“…There are also literature reports of trisomy 12, trisomy 14, and loss of chromosome 16, although these CNVs were less frequent in our study. This discrepancy might be due (at least in part) to the number of samples used in the literature studies (10, 15, and 21 samples in references [10,11,14], respectively) or by the high proportion of recurrent tumors in our series [15]. When calculating the GI for each sample, we could not determine a predictive cut-off.…”
Section: Chromosome Instability In Recurrent Agctsmentioning
confidence: 89%
“…Our analyses revealed that, consistent with primary PACs, recurrent PACs showed the canonical alterations affecting PRKD genes, including PRKD1 hotspot E710D mutations or a PRKD2 rearrangement. The maintenance of the highly recurrent/pathognomonic genetic alteration that characterises these tumours in the recurrences and after the acquisition of high-grade histological features is consistent with the observations made in other tumour types driven by pathognomonic genetic alterations, [41][42][43][44] and is consistent with the notion that these alterations constitute drivers of the disease. For instance, in the progression of adenoid cystic carcinomas to high-grade tumours, the MYB-NFIB fusion gene is maintained 41 ; likewise, in the progression of granulosa cell tumours, the FOXL2 C134W mutation is conserved.…”
Section: Discussionsupporting
confidence: 88%
“…The maintenance of the highly recurrent/pathognomonic genetic alteration that characterises these tumours in the recurrences and after the acquisition of high‐grade histological features is consistent with the observations made in other tumour types driven by pathognomonic genetic alterations, and is consistent with the notion that these alterations constitute drivers of the disease. For instance, in the progression of adenoid cystic carcinomas to high‐grade tumours, the MYB–NFIB fusion gene is maintained; likewise, in the progression of granulosa cell tumours, the FOXL2 C134W mutation is conserved . Consistent with the notion that, in the progression of tumours driven by pathognomonic mutations, additional genetic alterations are acquired or subclonal genetic alterations present in minor subclones of the primary tumour are selected, we observed that the recurrent tumour RS1‐T2 acquired additional subclonal ERBB2 (V839M) and ZFHX3 (G3527dup) mutations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation